Distributed systems architecture a middleware approach - Puder, Arno.; Romer, Kay.; Pilhofer, Frank (Amsterdam ; Boston : Elsevier : Morgan Kaufmann, 2006)
Middleware is the bridge that connects distributed applications across different physical locations, with different hardware platforms, network technologies, operating systems, and programming languages. This book describes middleware from two different perspectives: from the viewpoint of the systems programmer and from the viewpoint of the applications programmer. It focuses on the use of open source solutions for creating middleware and the tools for developing distributed applications. The design principles presented are universal and apply to all middleware platforms, including CORBA and Web Services. The authors have created an open-source implementation of CORBA, called MICO, which is freely available on the web. MICO is one of the most successful of all open source projects and is widely used by demanding companies and institutions, and has also been adopted by many in the Linux community. * Provides a comprehensive look at the architecture and design of middleware--the bridge that connects distributed software applications * Includes a complete, commercial-quality open source middleware system written in C++ * Describes the theory of the middleware standard CORBA as well as how to implement a design using open source techniques.
Preface; 1 Introduction; 2 Basic Concepts; 3 Introduction to CORBA; 4 ORB; 5 ORB Design; 6 Interoperability; 7 Object Adapters; 8 Invocation Adapters; 9 IDL compiler; 10 CORBA and Beyond; Appendix A MICO Installation; B Mico Implementation Overview; C Mico Implementation Details; D Sample Application; List of Figures; Glossary; Bibliography; Index.
Includes bibliographical references (p. 313-315) and index.
Keywords: Electronic data processing -- Distributed processing; Computer architecture; CORBA (Computer architecture).; Electronic books